DESIGN AND FABRICATION OF RADIAL FLUX PERMANENT MAGNET GENERATOR FOR WIND TURBINE APPLICATIONS - Ashraf, M. M.; Malik, T. N.; Zafar, S.; Raja, U. N. (The Nucleus, 2013)
Presently alternate energy resources are replacing conventional energy sources to produce electrical power to minimize the usage of fossil fuels. Wind power is one of the potential alternate energy resources and is being exploited and deployed actively. The wind energy system is basically composed of two core components: wind turbine and electrical generator. This paper presents the design and fabrication of permanent magnet generator for direct drive wind turbine applications. Radial flux permanent magnet generator (RFPMG) producing three phase alternating current voltage has been designed subject to satisfying the features of low operating shaft speed, higher power density, higher current density, cost effectiveness and compact structure. RFPMG design focuses on usage of neodymium permanent magnets for excitation instead of electromagnets to minimize the excitation arrangement challenges and losses. A 300 W prototype RFPMG has been fabricated. The performance of the generator has been evaluated on specially designed wind tunnel. The generator is directly coupled with wind turbine shaft to eliminate the gearbox losses. No load and load tests show that the performance of the machine is up to the mark. The improved design parameters of power density and current density are 73.2 W/kg and 5.9 A/mm2 respectively. The same machine output has been rectified using bridge rectifier for battery charging application. The desired output voltages are obtained at minimum shaft speed of the generator. Thus the design of generator confirms its application with small scale domestic wind turbines producing direct current supply.